2016
DOI: 10.1152/ajpendo.00415.2015
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine regulation of glucagon secretion: the β/α/δ model

Abstract: The regulation of glucagon secretion in the pancreatic α-cell is not well understood. It has been proposed that glucose suppresses glucagon secretion either directly through an intrinsic mechanism within the α-cell or indirectly through an extrinsic mechanism. Previously, we described a mathematical model for isolated pancreatic α-cells and used it to investigate possible intrinsic mechanisms of regulating glucagon secretion. We demonstrated that glucose can suppress glucagon secretion through both ATP-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 83 publications
(114 reference statements)
2
40
0
1
Order By: Relevance
“…We used our large dataset to improve the fit of a conductance-based model of a δ-cell to the experimental data. The δ-cell model of Watts et al [75] was used as the starting model. ( a ) The model was simulated under a Na + current inactivation voltage-step protocol ( V cond = −180 to 20 mV followed by a test pulse to 0 mV), and the evoked Na + current in the model (solid) was compared with the inward current experimentally recorded from a δ-cell under the same protocol (dashed).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used our large dataset to improve the fit of a conductance-based model of a δ-cell to the experimental data. The δ-cell model of Watts et al [75] was used as the starting model. ( a ) The model was simulated under a Na + current inactivation voltage-step protocol ( V cond = −180 to 20 mV followed by a test pulse to 0 mV), and the evoked Na + current in the model (solid) was compared with the inward current experimentally recorded from a δ-cell under the same protocol (dashed).…”
Section: Discussionmentioning
confidence: 99%
“…The currents shown are in response to V cond = −150, −100, −60 and −20 mV. ( b ) Spiking behaviour generated by the model of Watts et al [75] with the reparametrized Na + current model (as shown in a ) and C cell = 4 pF was compared with the original, unaltered δ-cell model by Watts et al [75]. Note that action potentials evoked in the improved model overshoot 0 mV, have short duration and also have a pronounced after-hyperpolarization (arrows; owing to the A-type K + current), as seen in the experimental action potentials recorded from a δ-cell under the perforated patch-clamp configuration ( c ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1-Some controls of glucagon secretion that may be involved in glucagon nonsuppression or tonically increased fasting glucagon levels in insulin resistance or diabetes (note that receptor mechanisms are not shown). As reviewed in detail elsewhere (1)(2)(3)(4)(5)(26)(27)(28), nutrient, neural, endocrine, paracrine, and autocrine effects control glucagon secretion. The dynamic interactions among these controls are poorly understood.…”
mentioning
confidence: 99%